Austenitic Stainless Steels - New Aspects - Tomasz Tanski; Wojciech Borek; Zbigniew Brytan (IntechOpen, 2017)
Stainless steel is still one of the fastest growing materials. Today, the austenitic stainless steel with the classic composition of 18% Cr and 8% Ni (grade 304L) is still the most widely used by far in the world. The unique characteristic of stainless steel arises from three main factors. The versatility results from high corrosion resistance, excellent low- and high-temperature properties, high toughness, formability, and weldability. The long life of stainless steels has been proven in service in a wide range of environments, together with low maintenance costs compared to other highly alloyed metallic materials. The retained value of stainless steel results from the high intrinsic value and easy recycling. Stainless steel, especially of austenitic microstructure, plays a crucial role in achieving sustainable development nowadays, so it is also important for further generations.
English
Keywords: Physical Sciences; Engineering and Technology; Materials Science; Metals and Nonmetals; Metallurgy